THE EFFECT OF DIFFERENT TYPES AND RATES OF FERTILIZERS ON THE POPULATION DENSITY OF SAP SUCKING PESTS INHABITING COWPEA FIELDS - El-Khayat, E. F.; Mona M. Ghallab; Wahba S. (Arab Universities Journal of Agricultural Sciences, 2014)
This study was carried out during 2012 and 2013 seasons in the Horticultural Research Station at Kanater El- Khairiya, Qualiobeya Governorate to throw light on the effect of different types and rates of fertilizer treatments on the rates of infestation of the cowpea plants, Vigna unguiculata L. by different pests Tetranychus urticae, T. cucurbitacearum (eggs and motile stages), Bemisia tabaci (eggs, nymphs, pupae & adults), Thrips tabaci (nymphs & adults) and green Jassids and on the resultant crop yield. Data revealed that treatment with NPK mixture recorded the highest infestation rate by T. urticae Koch, T.cucurbitacearum (Sayed) and T. tabaci in the two seasons, while the K2O fertilizer revealed the lowest infestation rates. Moreover, the N2 fertilizer recorded the highest infestation with whitefly and Jassids. The brown scale insects, Coccus hesperidium Linnaeus were firstly recorded in Egypt on cowpea plants but throughout the first season only. The mixture treatments resulted highest yield (2428.3 &2675 Kg./fed.) followed by Micro-element treatments (1500 &1658.3 Kg./fed.) then K2O fertilizer treatment (1416.7 & 1553.3 Kg. /fed.) in 2012 and 2013, respectively; being significantly higher than control which recorded (756.0 & 845.0 Kg. / fed.) for the two seasons.   However, the results showed a significant improvement in the uptake of NPK over the control, so it increased the production.